2002
DOI: 10.1023/a:1022909127992
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Serum MDA level and concentration of superoxide anion in leukocytes were measured in patients with acute hepatitis B and C at the peak of the disease, during regression, and during early convalescence. The concentration of active oxygen forms in leukocytes was maximum at the peak of the disease and decreased before discharge from the hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Moreover, in a study on patients with HBV-associated HCC, significant elevation of superoxide anion radicals was observed (29). This increase in superoxide anions was also seen in the leukocytes of patients with CVHB (75). Although this parameter is difficult to measure, further studies in this field could reveal correlations between ROS/RNS production and hepatitis B disease activity.…”
Section: Resultsmentioning
confidence: 63%
“…Moreover, in a study on patients with HBV-associated HCC, significant elevation of superoxide anion radicals was observed (29). This increase in superoxide anions was also seen in the leukocytes of patients with CVHB (75). Although this parameter is difficult to measure, further studies in this field could reveal correlations between ROS/RNS production and hepatitis B disease activity.…”
Section: Resultsmentioning
confidence: 63%
“…There are some studies in the literature that investigated MDA in plasma, serum and erythrocytes of patients with hepatitis. It was demonstrated that serum MDA level was increased in patients with HCV during regression and early convalescence [19]. In liver damage caused by viral etiology, it is reported that the MDA level increases in serum and liver tissue.…”
Section: Discussionmentioning
confidence: 99%